OPTIMIZING OUR NETWORKED LIVES - McKelvey, Fenwick; Carmi, Elinor; ten Oever, Niels; Gürses, Seda (AoIR Selected Papers of Internet Research, 2020)
We use the term networked optimization to emphasize a sustained but changing set of techniques, technologies, and calculations to decide the best life -- the optimal -- through infrastructures, design, mathematics and engineering. Optimization is a vital concept at a time of critical interest in infrastructural power. Usually defined as doing actions to make the best or most effective use of something, our panel highlights the different uses of the term across the internet. Used as a selling point by many technology companies, optimization means different things to different actors. Perhaps the most important question on this is optimized for who? From Facebook to 5G, our panelists work across technical and theoretical literatures as well as computer science and humanities to identify the social implications of networked optimization. Author #1 examines how Facebook’s personalization ideology is engineered into its infrastructure to influence people’s behaviors to maximize its advertising value. Author #2 looks to the discourses and infrastructure of Google’s cloud computing that promise a form of global social engineering. Author #3 takes these questions out of the cloud and into the next-generation of the Internet, 5G. The promised new wireless infrastructure makes a major shift in the meta-governance of communications and re-consolidates power in network operators. Finally, Author #4 looks for forms of resistance through the development of Protective Optimization Technologies that help people counter efforts to nudge and shape their behaviours.